Combinatoric Drag–Pattern-Graphical-Password (DPGP) - Sylla, Mohamed; Muhammad, Gul; Habib, Kaleem; Ibrahim, Jamaludin (CIS Journal, 2013)
Creating secure password has been limited attributable to password restriction and policy. Users tend to choose memorable passwords that are easy to guess. However, sophisticated systems assigned passwords that are difficult to remember. In this paper, the focus will be on the Drag–pattern-Graphical-Password (DPGP). DPGP password is proposed technique of protecting systems with a password that combines drag button technique, pattern and text-based password authentication. The purpose is to create more secure password and somewhat easy to remember but difficult to hack. A relevant usability of authentication systems is to assist users of selection strong password, therefore improving security by augmenting the effectiveness of passwords encryption. However, with the most secure system, Users are often seen as the weakest point of the system, willing to circumvent security policies in order to access their work faster, users don’t really pay attention to the strength of their password. Thus, to build infallible authentication system, we use persuasion to influence users’ choice with Drag–pattern-Graphical-Password (DPGP) engaging them to select more random characters, hence difficult to guess.